173 EFFECT OF PRENATAL COCAINE EXPOSURE ON THE STRESS AXIS IN YOUNG ADULT RATS. (1st January 2005) - Sithisarn, T.; Bada, H.; Randall, D.; Brown, D.; Kim, M.; Legan, S.
Abstract : Exposure to prenatal stress may result in childhood behavioral problems, due to in utero programming of hypothalamic-pituitary-adrenal axis (HPA). A stress, prenatal cocaine exposure, may alter the fetal HPA development, which may play a role in the abnormal behavior in children of cocaine-abusing mothers. Objective: We determined the effects of prenatal cocaine exposure on the responsiveness of the HPA axis to stress. We hypothesized that prenatal cocaine exposure will alter the HPA response to stress. Material and Methods: Pregnant Sprague-Dawley rats were given cocaine (2 mg/kg/d, 1 ml/kg) or normal saline (NS) (1 mL/kg) IV from gestational day (GD) 8 to GD 22. Mixed gender litters were culled to 11 and weaned at postnatal day (PD) 28. At PD 45, ovine CRF was injected IV to male and female rats exposed to either prenatal cocaine (n = 22) or NS (n = 20). Blood samples were drawn before and at 15, 30, 60 minutes post injection. To control for stress from handling and blood sampling, NS was administered and blood samples were obtained in additional rats exposed to either cocaine (n = 22) or NS (n = 20). Corticosterone levels were determined by RIA. The longitudinal data were analyzed with a linear mixed model. Results: Weights (birth through adulthood) were not different between cocaine- and NS-exposed rats. Cocaine-exposed and NS-exposed rats both responded to either CRH or NS injection but CRH injection caused a greater increase in plasma corticosterone than NS (p < .0001). At baseline, cocaine-exposed females had higher corticosterone levels than NS-exposed rats (p = .016); these were observed in male rats, but not significantly different (p = .4278). In female rats, cocaine effect diminished (in the CRH-injected rats) or reversed (in the NS-injected rats) between 30 and 60 minutes (p = .049) while corticosterone levels in cocaine-exposed males stayed higher than NS-exposed rats. Female rats had higher corticosterone levels than males, regardless of prenatal exposure or injection of CRH or NS (p < .0001). Conclusion: Corticosterone reactivity to stress is not abolished by prenatal cocaine exposure. However, in female rats, cocaine exposure resulted in altered pattern of corticosterone response to stress. The mechanisms for these findings and their significance remain to be determined.